ETHNOBOTANICAL AND PHARMACEUTICAL USES OF VETIVERIA ZIZANIOIDES (LINN) NASH: A MEDICINAL PLANT OF RAJASTHAN: Life Science-Botany - PAREEK, ARCHANA; ASHWANI KUMAR (International Journal of Life Science and Pharma Research, 2013)
Wetlands provide a unique habitat for several medicinal plants. Attempt has been made to document some of the little known medicinal properties of wetland plants used by local community of India. Vetiveria zizanioides (L.) Nash synonymously known as Chrysopogon zizanioides (L) Roberty (Family: Poaceae/Gramineae) is widely cultivated in the tropical regions of the world. The plant has a unique characteristic of being xerophyte (tolerates prolonged drought) but it survive under long seasonal flooding; it tolerates extreme temperature and grows over a wide range of soil pH. A perennial aromatic grass grows up to 2 meter in height. Vetiver has been known in India from the ancient times. It is known as Khas-Khas and is widely used as cooling agent, tonic and blood purifier. It is used to treat many skin disorders and is known to have calming effect on the nervous system. Other medicinal uses of Khas Khas include ringworm, indigestion and loss of appetite. It has been considered a high-class perfume. Though the aquatic situations of India are rich repositories of various plant species, not much work has been under taken to enumerate the medicinal uses of them